Joint statement for assessing and managing high blood pressure in children and adolescents: chapter 2. How to manage high blood pressure in children and adolescents - Wühl, Elke; Calpe, Javier; Drożdż, Dorota; Erdine, Serap; Fernandez-Aranda, Fernando; Hadjipanayis, Adamos; Hoyer, Peter F.; Jankauskiene, Augustina; Jiménez-Murcia, Susana; Litwin, Mieczysław; Mancia, Giuseppe; Mazur, Artur; et al. (Frontiers in Pediatrics, 2023)
The joint statement is a synergistic action between HyperChildNET and the European Academy of Pediatrics about the diagnosis and management of hypertension in youth, based on the European Society of Hypertension Guidelines published in 2016 with the aim to improve its implementation. Arterial hypertension is not only the most important risk factor for cardiovascular morbidity and mortality, but also the most important modifiable risk factor. Early hypertension-mediated organ damage may already occur in childhood. The duration of existing hypertension plays an important role in risk assessment, and structural and functional organ changes may still be reversible or postponed with timely treatment. Therefore, appropriate therapy should be initiated in children as soon as the diagnosis of arterial hypertension has been confirmed and the risk factors for hypertension-mediated organ damage have been thoroughly evaluated. Lifestyle measures should be recommended in all hypertensive children and adolescents, including a healthy diet, regular exercise, and weight loss, if appropriate. If lifestyle changes in patients with primary hypertension do not result in normalization of blood pressure within six to twelve months or if secondary or symptomatic hypertension or hypertension-mediated organ damage is already present, pharmacologic therapy is required. Regular follow-up to assess blood pressure control and hypertension-mediated organ damage and to evaluate adherence and side effects of pharmacologic treatment is required. Timely multidisciplinary evaluation is recommended after the first suspicion of hypertension. A grading system of the clinical evidence is included.